Use of biological control agents for managing fungal pathogens in Solanaceae crops: progress and future perspectives—a review - Sinhle Madlhophe; Udoka Vitus Ogugua; Fikile Nelly Makhubu; Sandiswa Figlan (Discover Applied Sciences)
Abstract The growing global population has intensified concerns about food security, making it essential to produce crops sustainably to meet increasing demands without harming the environment. In this regard, biological control agents (BCAs) have recently gained more attention owing to their potential to manage fungal diseases of crops, particularly in the Solanaceae family. The proper use of selected BCAs such as Trichoderma spp., Bacillus spp., Pseudomonas fluorescens, Beauveria bassiana, and Gliocladium spp. has several benefits for Solanaceae crops. This review aims to summarize the effectiveness of various biological control strategies for fungal diseases in Solanaceae crops. We also provide basic knowledge on BCAs along with suggestions for further research to reduce the severity of these destructive diseases.